Psychometric evaluation of the Malay version of the Montgomery-Asberg Depression Rating Scale (MADRS-BM) - Yee, Anne; Mat Yassim, Abdul Rahim; Loh, Huai Seng; Ng, Chong Guan; Tan, Kit Aun (BioMed Central, 2015)
Background: This study examines the psychometric properties of the Malay version of the Montgomery-Ǻsberg Depression Rating Scale (MADRS-BM). Methods: A total of 150 participants with (n = 50) and without depression (n = 100) completed the self-rated version of the Montgomery-Ǻsberg Depression Rating Scale (MADRS-S), the Malay versions of the MADRS-BM, the Beck Depression Inventory-II (BDI-II-M), the General Health Questionnaire-12 (GHQ-12), and the Snaith-Hamilton Pleasure Scale (SHAPS-M). Results: With respect to dimensionality of the MADRS-BM, we obtained one factor solution. With respect to reliability, we found that internal consistency was satisfactory. The scale demonstrated excellent parallel form reliability. The one-week test-retest reliability was good. With respect to validity, positive correlations between the MADRS-BM, BDI-II-M, and the GHQ and negative correlation between the MADRS-BM and SHAPS-M provide initial evidence of MADRS-BM’s concurrent validity. After adjusting for age, gender, ethnicity, educational level, and marital status, individuals with depression significantly reported higher MADRS-BM scores than did individuals without depression. Hence, there is additional evidence for concurrent validity of the MADRS-BM. Cut-off score of 4 distinguished individuals with depression from individuals without depression with a sensitivity of 78 % and a specificity of 86 %. Conclusions: The MADRS-BM demonstrated promising psychometric properties in terms of dimensionality, reliability, and validity that generally justifies its use in routine clinical practice in Malaysia.